شرح ِ حدیث میں شیخ محی الدین ابن عربی ﷫ کےمنہج و اسلوب کا تجزیاتی مطالعہ: Mohiuddin Ibn Arabi’s Methodology of Hadith Interpretation: An Analytical Study DOI:10.5281/zenodo.8134678 - Sayyed Sadaqat Ali Shah Bukhari; Yasir Arfat (Peshawar Islamicus, 2023)
The science of Tasawwuf (Sufism) is representative of the spiritual aspect of Islam. The history of Islamic Sciences shows that Sufi Saints of different ages contributed a lot to all the sciences and vital disciplines of Islam. We find Quranic Commentaries, Hadith Interpretations, Books on Islamic Fiqh and Islamic Jurisprudence and in other different areas written by Sufi Saints like Hasan Basri, Haris Al-Muhaasbi, Junaid Baghdadi, Siraj Al-Tusi, Abu Talib Makki, Abdul Qadir Jilani and Ibn Arabi etc. Ibn Arabi is one of the eminent Sufi saints who is familiar for his Sufi philosophy. Like his other major contributions, Ibn Arabi also contributed a lot to the field of Hadith. His interpretations of Hadith texts explore distinctive shades and layers of the prophet’s traditions. In this article, we explored his methodology of interpretation of Ahadith, focusing on two important books of Ibn Arabi titled al-futuhat al-makkiyya and Al-Mahajjat al Bayza. Keywords: Hadith,Ibn Arabi,Taswwuf,Saint,Methodology شریعتِ اسلامیہ